Antibiotic management of native mitral valve infectious endocarditis in patient with unaffected prosthetic aortic valve: A case report (Indian Journal of Case Reports, 2024)
Infectious endocarditis is a rare but feared condition, most frequently caused by Staphylococcus aureus. We describe the case of an 81-year-old male patient presenting with intermittent fever and dyspnea. Cardiac evaluation with transthoracic echocardiogram showed the presence of heart failure with suspicion of endocarditis. Consequently, a transesophageal echocardiogram demonstrated vegetation on the native mitral valve with an unaffected prosthetic aortic valve. Blood cultures were positive for S. aureus. Literature concerning endocarditis originating from a native valve in patients with a prosthetic valve is limited. We applied a new treatment scheme consisting of intravenous floxapen 12 g/24 h in a continuous infusion combined with intravenous rifampicin 2×300 mg daily for a duration of 6 weeks resulting in complete regression of the vegetation. In addition, we were successful in preventing disease propagation to the prosthetic valve. There is a need for more adequate research to prove the prophylactic benefit of this treatment.